Quality of life in people with syndromic heritable thoracic aortic disease and their relatives: a qualitative interview based study - Gry Velvin; Heidi Johansen; Gunnbjørg Aune; Kerstin Fugl-Meyer; Amy Østertun Geirdal (Orphanet Journal of Rare Diseases)
Abstract Introduction The purpose of this study was to investigate perceptions and opinions on what constitutes determinants for quality of life (QoL) in individuals with syndromic Heritable Aortic Disease (sHTAD), utilizing a qualitative study approach. Further to discuss clinical implications and direction for research. Method A qualitative focus group interview study was conducted of 47 adults (Marfan syndrome (MFS) = 14, Loeys-Dietz syndrome (LDS) = 11, vascular Ehlers Danlos syndrome (EDS) = 11, relatives = 11). The interviews were digitally recorded and transcribed verbatim. Significant themes were identified, extracted, and organised undergoing content analyses. Results The two main themes and 10 subthemes identified; I. Psychosocial well-being; (i) Social engagement and activity, (ii) Self-sufficient in daily living, (iii) Participation in education and work life, (iv) Coping with fear related to the disease, (v) Being able to control and accept fatigue and pain, (vi) Maintaining active engagement with family and friends (vii) Finding health-promoting physical activities. II. Monitoring and meetings with the health service: (viii) Feeling safe and receiving coordinated care, (ix) Being recognized, seen, and accepted, (x) Receiving factual and sober information and advice. The sub-themes seemed mutually interrelated in terms of barriers, strategies, and facilitators for improving quality of life. There was high degree of consensus regarding the factors emphasized as important for QoL among the various diagnostic groups and the relatives. Conclusion Based on our findings, to improve QoL in patients with sHTAD we should more effectively integrate the patient`s perspectives and voice on the elements crucial to QoL. In addition, it is vital for developing and customizing validated questionnaires to accurately reflect the factors deemed significant by this specific patient cohort. The research is limited on patients’ perspectives on QoL, and more research is warranted. This might also be crucial for identifying relevant validated QoL instruments that reflect the patients` perceptions of what is vital for QoL.